The life and work of Khabi Mngoma - Burger, Inge Mari (College of Music, 2021)
The thesis intends to describe the life and work of Khabi Mngoma, protagonist of black music education in South Africa (latter half of the twentieth century), with reference to historical, socio-political, anthropological, educational and musicological aspects. His musical development from a mere participator in musical activities of his environment to a dominantly influential initiator of cultural and musical activities and education programmes on a national scale, is investigated. The study is presented in thirteen chapters: the first three chapters explore the musical influences of Khabi Mngoma's childhood (in the township-, school-and rural environment respectively), and the musical influences of his early adulthood. Particular, reference is made to his first academic musical studies in Western classical music, and the arousing of his interest in the academic study and performance of African music. The following nine chapters describe Khabi Mngoma's cultural and music educational activities (1948 - 1990) and explore the growing recognition of him as a cultural and music educational leader in South Africa. This period of Khabi Mngoma's life and work is divided into five periods: his work in Orlando, Soweto and Johannesburg during the years of his association with the Orlando High School (1948 - 1952; the first period); the second period refers to Khabi Mngoma's Social and Cultural work for the National War Memorial Health Foundation (1953 - 1957); the third, fourth and fifth periods relate to Khabi Mngoma's cultural and educational activities associated with the periods of employment by the Johannesburg City Council (1957 - 1964; third period), Dorkay House (Union Artists) and Reckitt & Colman (1965 - 1975: simultaneous employment; fourth - period), and finally the University of Zululand (1975 - 1987; the fifth period). The fifth period continues into the years following his retirement in 1987, with his influence on a national scale continuing to be established through various significant involvements, discussed in this study. The decision to arrange Khabi Mngoma' s adult life and career into five periods needs explaining. I am aware that human endeavor can never be neatly compartmentalized, because so many aspects of such endeavour overlap. This format is not intended to imply a rigid delineation; it is derived from the chronological arrangement of my material, and is intended to guide the reader through this study.